(3LhGgQ GdHMGQ aj fXe SjQI GdoeNJGQs - (3GdHbGYj , EHQGgje Hf YeQ Hf MSf GdQHGW Hf Ydj Hf CHj HcQ GdHbGYj GdTGaYj, HQgGf GdOjf CHh GdMSf,J (B885 (3g` s
(3ChdgG (B:s
(3eGHGd Lafc gGei GdOeY gGeQg hHMQ acQc hGaj Gdge hGaQI s
(3BNQgG (B:s
(3CQLh ceG Rjf GdEjeGf Chdg Gf jSJJe HMSf GdNJe BNQg s
(3hgj bUjOI aj GdSjQI GdfHhjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3fXes
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs